STI in history: Korean STI policies in the institutional building stage - Hwan, Youngsoo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Korea is surging as a strong technological country that competes with technology advanced countries and is positioned as one of world top 10 countries in terms of economic volume. Korean products, traditionally seen as cheap imitations, now occupy advanced product areas in foreign sales rooms and have globally established Korean products as technologically advanced. Many still remember the devastation of the Korean War; however, it is marvelous to see Korea’s remarkable current developments. It is unprecedented for an underdeveloped country to enter the ranks of an advanced country in such a short time. In addition, it is miraculous for a country to develop advanced technologies in 50 years from the state where it had almost no modern S&T capacities. The marvelous advancement of Korea was possible to the successful execution of export-oriented economic development and the advancement of educational system to develop competent human resources; however, they cannot be fully explained without explaining the development of modern Korean S&T. This paper examines the contexts and implementation efforts of major S&T policies in the 1960s and 1970s when Korea started S&T development with domestic efforts to support industrialization and achieved the rapid economic growth known as the "Miracle of Han River". This paper also assesses outcomes of S&T policies in that period and suggests some implications to developing countries.